Metode Perolehan Data Luasan Lahan Sawah yang Akurat Berbasis Sistem Informasi Geografis di Kabupaten Maros - Herman Halim; Amal Said; Awaluddin Yunus (Lembaga Pengembangan Kinerja Dosen, 2025)
Accurate paddy field area data is a crucial factor in agricultural development planning, particularly as a basis for formulating data-driven programs and policies. One of the main problems encountered at the regional level is the continued reliance on administrative data that does not fully reflect actual field conditions due to land use changes, boundary inaccuracies, and limited verification processes. This study aims to determine an appropriate method for obtaining accurate paddy field area data through the application of Geographic Information Systems (GIS) in Maros Regency. The research employed a descriptive quantitative approach using spatial analysis methods. The data utilized consisted of Paddy Field Base Data, National Geospatial Base Maps, high-resolution satellite imagery, and field verification data. Spatial analysis was conducted through digitization, overlay, intersect, and area calculation processes using ArcMap 10.8 software. The results indicate that GIS-based spatial analysis produces more accurate and verified paddy field area data compared to conventional administrative data. The integration of spatial data with field verification effectively minimizes measurement errors and boundary discrepancies. This method can serve as a reliable reference for providing accurate agricultural base data to support planning and policy-making in the agricultural sector.